Two new species of the genus Austrocotesia Austin & Dangerfield (Hymenoptera: Braconidae) from the Andean region of South America - Valerio, A. A.; Whitfield, J. B. (Zootaxa, 2005)
The microgastrine braconid wasp genus Austrocotesia was erected by Austin & Dangerfield as a new, apparently endemic Australasian genus. In the past 8 years a series of specimens clearly belonging to the genus have been collected throughout South America and Mesoamerica. In the present paper, Austrocotesia croizati n. sp. and A. renei n.sp. are described and illustrated from the Andean region of South America. In addition, a key to the known species is presented, and the relationships and taxonomic status of the genus are briefly discussed.